An Analysis of Figurative Language Commented by Peter Drury in World Cup Final Matches in 2014, 2018, and 2022 - Azra, Syaifatul; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
This thesis explores the use of figurative language in football commentary, focusing on Peter Drury's commentary on the 2014, 2018, and 2022 World Cup final matches. This study aims to identify and analyze the types of figurative language and meanings used by Peter Drury during the 2014, 2018, and 2022 World Cup final matches. A qualitative descriptive approach was employed, using Abrams and Harpham's theory to analyze figurative language, alongside Leech's theory for meaning. Out of 53 instances of figurative language, metaphor emerged as the dominant type in each World Cup final edition, appearing 11 times in 2014, 11 times in 2018, and 10 times in 2022, totaling 32 times (60.38%). The connotative meaning was the most prevalent among the seven types of meaning, occurring 29 times (54.72%). Types of figurative language such as alliteration, onomatopoeia, litotes, and euphemisms were not found in this study. The type of meaning that was not found reflected meaning. This analysis reveals a change in the pattern of Peter Drury's figurative language use in the last three editions of the World Cup finals, in addition to metaphors that appear dominant each year, hyperbole has decreased significantly in the three editions of the World Cup finals. In 2014 it was found 6 times, in 2018 it was found 3 times, and in 2022 it was found 2 times. This analysis also highlights the role of figurative language in creating an immersive experience for the audience.